2009
DOI: 10.1080/09084280802644144
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cognitive, Personality, and Background Factors on the WAIS-III Arithmetic Subtest

Abstract: In the Wechsler system the Arithmetic subtest has been viewed as a measure of concentration, working memory, or freedom from distractibility. However, a wide range of other influences on Arithmetic performance has been proposed. The current study was intended to examine these to further characterize what is measured by the Arithmetic subtest. Participants were 118 adults referred for neuropsychological assessment. The results indicate a strong association between WAIS-III Arithmetic and the other WMI (Working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…That is, the elderly participants were trained on a visual/spatial task while the transfer task of letter–number sequencing was auditory/verbal, suggesting that the transfer effect is supramodal in nature. This finding interestingly paralleled the supramodal transfers observed for working memory training that accompanied changes in brain activity in supramodal working memory-related regions (Olesen et al, 2004; Karzmark, 2009; Smith et al, 2009; Borella et al, 2010). …”
Section: Resultssupporting
confidence: 66%
“…That is, the elderly participants were trained on a visual/spatial task while the transfer task of letter–number sequencing was auditory/verbal, suggesting that the transfer effect is supramodal in nature. This finding interestingly paralleled the supramodal transfers observed for working memory training that accompanied changes in brain activity in supramodal working memory-related regions (Olesen et al, 2004; Karzmark, 2009; Smith et al, 2009; Borella et al, 2010). …”
Section: Resultssupporting
confidence: 66%
“…When a problem can be solved by either verbal computation or spatial imagery, males are more apt to use the latter (Geary, Saults, Liu, & Hoard, 2000). An analysis of students' achievements on the arithmetic subset of the Wechsler scales showed a high association of test scores with both arithmetic skills and verbal memory (Karzmark, 2009). The association between the level of reading in early elementary school and progress in mathematics was shown to be higher among girls than among boys (Grimm, 2008).…”
Section: Spatial and Verbal Skills In Relation To Mathematics Achievementioning
confidence: 99%
“…In reevaluating a hypothesized CFA structure for the WAIS-IV, the controversies mentioned above and in particular previous studies shown in Table 1 were used as a guide. Studies of previous and current versions of Wechsler scales have found that a number of broad abilities influence scores on Arithmetic, both in clinical and healthy community populations and across cultures (Canivez & Kush, 2013; Georgas, Weiss, van de Vijver, & Saklofske, 2003; Karzmark, 2009; Sattler & Ryan, 2009). In the fourth edition of the WAIS efforts have been made to concentrate on the working memory load in Arithmetic, and reduce demands on verbal comprehension, mathematical knowledge, and processing speed in completing Arithmetic (Wechsler, 2008a).…”
mentioning
confidence: 99%